Pokok pokok kesehatan jiwa/mental - Abdul Aziz el Quussy (Bulan Bintang, 1975)
ast jil.1 = c.1-7 jil. 2 =c.1-5/oen, jil.1=c.8-9/ ir, jil.1,c.10-11/tr, jil.1=c.12-13/ast, jil.2 =c.6/ad, jil.1.c.14/stoc1,jil.1,c.1-12 ; jil.2,c.1-6/oen, jil.1, c.13